The Influence of Student Purchasing Power on Traders' Income in the Environment Around Campus - Vera Maria; Desi Maryana; Raisyha Rafania; M. Vhikry Salam (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was conducted with the aim of knowing the magnitude of the influence of the importance of student purchasing power on the economy, especially traders who are around them. With the formulation of the problem includes where student pocket money comes from, what is the average amount of student money each month, what is the money for, and what is the effect of student purchasing power on traders around the campus. The research method used by researchers is a qualitative research method. The location of this research was conducted at Sultan Ageng Tirtayasa University, with the target respondents being students of S1 Management, D3 Marketing Management, and D3 Banking at Sultan Ageng Tirtayasa University. The number of samples used was 28% of 250 students so around 70 respondents were obtained. Data collection techniques were carried out by distributing questionnaire links to students which were conducted online, and conducting interviews with targets, namely traders around the Untirta campus which were conducted offline. From the results of the study, the researchers found that many students were aware of the influence of their purchasing power to improve the economy of traders around the campus. From the results of the interviews, it was found that respondents (traders) around the campus stated that the purchasing power of students greatly influenced the merchant's economy. One of the impacts is that by returning to offline lectures, students are able to provide profits to traders from 50% to 200%, which can help stabilize the merchant's economy.